2023
DOI: 10.1113/ep090755
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of group III/IV afferent feedback and respiratory muscle work on exercise tolerance in heart failure with reduced ejection fraction

Joshua R. Smith,
Jonathon W. Senefeld,
Kathryn F. Larson
et al.

Abstract: Exercise intolerance and exertional dyspnoea are the cardinal symptoms of heart failure with reduced ejection fraction (HFrEF). In HFrEF, abnormal autonomic and cardiopulmonary responses arising from locomotor muscle group III/IV afferent feedback is one of the primary mechanisms contributing to exercise intolerance. HFrEF patients also have pulmonary system and respiratory muscle abnormalities that impair exercise tolerance. Thus, the primary impetus for this review was to describe the mechanistic consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
(265 reference statements)
1
2
0
Order By: Relevance
“…These findings have important implications for older patients with hypertension as exaggerated cardiovascular responses to inspiratory muscle metaboreflex activation are important contributors to exercise intolerance and exertional symptoms for patients with CVD. 3 Further, the present findings are directionally consistent with those recently reported in heart failure with preserved ejection fraction 4 ; a population with a high prevalence of hypertension. In this context, our findings suggest that these inspiratory muscle pathophysiologic mechanisms may present earlier in the CVD progression than previously recognized.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These findings have important implications for older patients with hypertension as exaggerated cardiovascular responses to inspiratory muscle metaboreflex activation are important contributors to exercise intolerance and exertional symptoms for patients with CVD. 3 Further, the present findings are directionally consistent with those recently reported in heart failure with preserved ejection fraction 4 ; a population with a high prevalence of hypertension. In this context, our findings suggest that these inspiratory muscle pathophysiologic mechanisms may present earlier in the CVD progression than previously recognized.…”
supporting
confidence: 92%
“… 2 Heart failure is also associated with pulmonary system abnormalities that directly relate to exercise intolerance and exertional symptoms including inspiratory muscle weakness and reduced inspiratory muscle endurance. 3 We found that inspiratory muscle metaboreflex activation via high inspiratory muscle work results in exaggerated increases in mean arterial pressure (MAP) and leg vasoconstriction, resulting in reduced leg blood flow in patients with heart failure compared with controls. 4 However, it is unclear whether these inspiratory muscle abnormalities are present earlier in the progression of CVD.…”
mentioning
confidence: 98%
See 1 more Smart Citation